Evaluation of Resin Bond Strength to Yttria-stabilized Tetragonal Zirconia and Framework Marginal Fit: Comparison of Different Surface Conditionings - Vanderlei, A. [UNESP]; Bottino, M. A. [UNESP]; Valandro, L. F. (Operative Dentistry Inc, 2014)
The purpose of this study was to evaluate the effect of different surface treatments of yttria-stabilized tetragonal zirconia (Y-TZP) on bond strength durability and marginal discrepancies. For adhesion testing, 144 specimens of VITA In-Ceram YZ ceramic for In Lab were obtained (5.25x3.75x4.5 mm) and divided into six groups (n=24) according to the surface treatment: 1) Control (CRTL): untreated; 2) SIL: tribochemical silica coating (CoJet system, 3M/ESPE AG); 3) V1+HF: spray application of low-fusing porcelain glaze (V1, VITA Akzent Spray Glaze) followed by etching with hydrofluoric acid (HF) (one minute); 4) V1+SIL: V1 glazing (VITA Akzent Spray Glaze) followed by tribochemical silica coating; 5) V2+HF: brush application of low-fusing porcelain glaze (VITA Akzent Glaze) plus etching with HF (one minute); and 6) V2+SIL: V2 glazing (VITA Akzent Glaze) plus tribochemical silica coating. After all treatments, the surfaces were silanized for five minutes (ESPE-SIL) and cementation was performed using Panavia F (Kuraray). Half of the specimens in each treatment were tested 24 hours after cementation (dry), with the other half subjected to storage (150 days) and thermocycling (12,000x) (aging), and then a shear test was carried out (1 mm/min). The micromorphological (digital optical profilometry and scanning electron microscopy) and elemental analyses of the treated surfaces were performed. The inner surfaces of 60 Y-TZP infrastructures were conditioned and marginal fit was evaluated. The statistical analysis revealed that the groups treated via surface glaze application followed by hydrofluoric acid etching and silanization showed the highest bond strength (in dry and aging conditions), but the bond strengths were affected by aging. The highest marginal discrepancies were observed in the groups receiving glaze (117.4 +/- 29.6 to 105.8 +/- 12.2 mu m) when compared to other groups (55.3 +/- 8.7 and 55 +/- 8.5 mu m). Low-fusing porcelain glaze + hydrofluoric acid etching changed the morphology of the Y-TZP ceramic and improved the adhesion to the resin cement, but obtaining high and stable bond values to Y-TZP remains challenging. Marginal discrepancies increased with glazing.